2015
DOI: 10.1007/s00253-015-6748-1
|View full text |Cite
|
Sign up to set email alerts
|

Profiling microbial community structures across six large oilfields in China and the potential role of dominant microorganisms in bioremediation

Abstract: Successful bioremediation of oil pollution is based on a comprehensive understanding of the in situ physicochemical conditions and indigenous microbial communities as well as the interaction between microorganisms and geochemical variables. Nineteen oil-contaminated soil samples and five uncontaminated controls were taken from six major oilfields across different geoclimatic regions in China to investigate the spatial distribution of the microbial ecosystem. Microbial community analysis revealed remarkable var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…Soil DNA Kit (OMEGA, Georgia, GA) as indicated in the instructions (Peng, Zi, & Wang, ). The V4 region of 16S rRNA gene was amplified by PCR using primers 515F (5′‐GTGCCAGCMGCCGCGGTAA‐3′) and 806R (5′‐GGACTACHVGGGTWTCTAAT‐ 3′) (Sun et al., , ). The primer pair has been shown to generate optimal community clustering with the sequence length in the V4 region (Caporaso et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Soil DNA Kit (OMEGA, Georgia, GA) as indicated in the instructions (Peng, Zi, & Wang, ). The V4 region of 16S rRNA gene was amplified by PCR using primers 515F (5′‐GTGCCAGCMGCCGCGGTAA‐3′) and 806R (5′‐GGACTACHVGGGTWTCTAAT‐ 3′) (Sun et al., , ). The primer pair has been shown to generate optimal community clustering with the sequence length in the V4 region (Caporaso et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…In order to determine the pH range (and optimum) for growth of strain F20-122 T , the isolate was cultured under the optimal salt concentration conditions, adjusting the medium to pH 5.0, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, and 10.0 with the addition of the appropriate buffers [56]. The optimal and range of temperature were determined by incubating strain F20-122 T under the optimal salt concentration and pH conditions, at temperatures of 4,15,20,25,30,37,40,45,50,55, and 60 • C. Growth rates were determined by monitoring the increase in the optical density at 600 nm.…”
Section: Phenotypic Characterizationmentioning
confidence: 99%
“…Besides, several studies have focused on the biotechnological potential of its enzymes [7][8][9][10][11][12][13][14][15]. On the other hand, several culture-independent studies have also shown the presence of members of the genus Natronomonas in different environments from widely separated sites, such as hypersaline and alkaline lakes, solar salterns, saline-alkaline soils, and sediments or oil fields [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], supporting the widespread distribution of species of this genus.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, these results suggesting a reduction of archaeal relative abundance in oil-contaminated soils from Trindade island are controversial to what was observed for Chinese oilfields contaminated soils, which detected an increase of archaeal sequences [121]. In this study, soils from six major oilfields in China were compared with undisturbed soils and the number of archaeal sequences, mostly associated to halophilic Euryarchaeota, was much higher in contaminated soils, suggesting that oil contamination may stimulate the enrichment of such archaea and indicating that, as proposed by other studies [122124], halophilic archaea may have a role in oil biodegradation in certain in situ geochemical conditions.…”
Section: Archaea In Soilsmentioning
confidence: 91%